Correlation Between Epicardial Fat Thickness Measured By Echocardiography And Coronary Artery Disease Severity Using The Gensini Score - Niazi, Gul Zaman Khan; Baig, Mirza Adnan; Ahmed, Zubair (Journal of Rawalpindi Medical College, 2025)
Objective: To investigate the relationship between epicardial fat thickness (EFT) and the severity of coronary artery disease (CAD) and determine an EFT cutoff value for CAD prediction. Materials and Methods: A correlational study was conducted at the Rawalpindi Institute of Cardiology with 113 patients undergoing coronary angiography. EFT was measured using echocardiography, and CAD severity was assessed using the Gensini Score. Pearson’s correlation and receiver operating characteristic (ROC) analysis were used for statistical evaluation. Results: A significant positive correlation was observed between EFT and Gensini Score (r = 0.749, p < 0.01). The EFT cut-off for predicting CAD was 4.50 mm, with a sensitivity of 89.8% and an area under the curve (AUC) of 0.920. Waist-to-hip ratio also correlated significantly with CAD severity, while BMI showed a weaker correlation. Conclusion: EFT is a reliable and non-invasive marker for CAD severity, with significant implications for risk assessment and management. MeSH Keywords: Epicardial Fat, Coronary Artery Disease, Gensini score